Determination of decision rules on the basis of genetic algorithms (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
Genetic algorithms have widely been used in optimization tasks, and there are only a few works that use genetic algorithms to find rules.